Essential oils as natural alternatives to growth promotors: the effect on growth performance, gut health, meat quality, and profitability in feedlot sheep - Maritz, Zane (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.